PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI PADA PT X JAKARTA PUSAT - Fadhel Adam Syahaical; Nur Achmad (JURNAL LENTERA BISNIS, 2025)
This study aims to analyze the impact of work discipline and motivation on employee performance, with job satisfaction acting as an intermediary variable. A quantitative research method was utilized in this investigation. The target population consisted of employees at PT X, located in Central Jakarta. The sampling process utilized a purposive sampling method, involving a total of 80 respondents. Data collection was conducted using a questionnaire formatted on a Likert scale. For data analysis, PLS technique was applied with the assistance of SMARTPLS 4.0 software. The PLS-SEM analysis consists of two main components: the Inner Model and the Outer Model. The result showed that motivation positively affects employee performance, but the impact is not significant. In contrast, work discipline has a positive and significant influence on employee performance. Moreover, both motivation and work discipline contribute positively and significantly to job satisfaction. Additionally, job satisfaction acts as a mediator in the relationship between motivation and work discipline with employee performance.